Pulmonary haemodynamics and mortality in chronic hypersensitivity pneumonitis. Issue 6 (21st June 2018) - Oliveira, Rudolf K.F.; Ota-Arakaki, Jaquelina S.; Gomes, Paula S.; Gimenez, Andrea; Messina, Carolina M.S.; Ramos, Roberta P.; Ferreira, Eloara V.M.; Systrom, David M.; Pereira, Carlos A.C.
Chronic hypersensitivity pneumonitis (CHP) is a common interstitial lung disease (ILD) frequently associated with lung fibrosis [1]. Among patients with CHP, the degree of pulmonary function impairment and the extent of fibrosis are known predictors of mortality [2, 3]. In other forms of ILD, such as idiopathic pulmonary fibrosis (IPF) and sarcoidosis, abnormal pulmonary haemodynamics measured during resting supine right heart catheterisation (RHC) are additionally associated with poor prognosis [4–7]. In CHP, however, the prognostic value of RHC is unknown. Indices of pulmonary vascular dysfunction are associated with mortality in chronic hypersensitivity pneumonitis http://ow.ly/1nwG30jwTSm